Extended Milstein Approximation to the Stochastic Allen-Cahn Equation with Random Diffusion Coefficient Field and Multiplicative Noise (Journal of Mathematical Study, 2023)
This paper studies the stochastic Allen-Cahn equation driven by a random diffusion coefficient field and multiplicative force noise. A new time-stepping scheme based on astabilized approach and Milstein scheme is proposed and analyzed. The proposed methodis unconditionally stable in the sense that a discrete energy is dissipative when the multiplicative noise is absent. The strong convergence rate of a spatio-temporal fully discretescheme is derived. Numerical experiments are finally reported to confirm the theoreticalresult and show that the new scheme is much more robust than the classical semi-implicitEuler-Maruyama scheme, especially when the interface width parameter is small.